Cognitive Science Perspectives on Verb Representation and Processing 2014
DOI: 10.1007/978-3-319-10112-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Verb Representation and Thinking-for-Speaking Effects in Spanish–English Bilinguals

Abstract: Does the language we speak influence how we think about the events in our experience? If so, do bilingual speakers construe the same event in different ways, depending on the language they use to verbally encode that event? Or does one of the languages play a more dominant role in influencing event construal? The present study investigates whether bilingual speakers attend to different aspects of a motion event, depending on the language they use to first describe that event. Specifically, we explore whether l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These findings echo those obtained by Lai and Narasimhan (2015) who examine how bilingual speakers of English and Spanish conceptualize motion events in a forced similarity judgment task. It is reported that bilinguals who describe a motion event in English in the first instance tend to select the event that has the same manner of motion as the target scene significantly more frequently than bilinguals who encode the same event in Spanish prior to judgment.…”
Section: Conceptualisation Of Motion Events In L1 and L2 Speakerssupporting
confidence: 85%
“…These findings echo those obtained by Lai and Narasimhan (2015) who examine how bilingual speakers of English and Spanish conceptualize motion events in a forced similarity judgment task. It is reported that bilinguals who describe a motion event in English in the first instance tend to select the event that has the same manner of motion as the target scene significantly more frequently than bilinguals who encode the same event in Spanish prior to judgment.…”
Section: Conceptualisation Of Motion Events In L1 and L2 Speakerssupporting
confidence: 85%
“…We manipulated bilinguals’ immediate language use with the test language by having them verbally describe the motion events in the test language prior to classifying motion events. During the experiment, a native Spanish or English experimenter chatted with the participants in the test language prior to the experimental task (Brown & Gullberg, 2011; Lai & Narasimhan, 2008) in order to put the bilingual participants in a “monolingual mode” (Grosjean, 2001, p. 5). Then, participants performed a similarity judgment task with verbal encoding.…”
Section: The Present Studymentioning
confidence: 99%